2019
DOI: 10.1002/app.48185
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the wicking behavior of micro/nanofibrous core‐sheath PET–PAN yarn modified by dimethyl 5‐sodium sulfoisophthalate

Abstract: The present research aims at imparting an improved wicking ability to the recycled multifilament yarns by wrapping composite nanofibers to attain an efficient material for filtration purposes. Therefore, polyacrylonitrile nanofibers containing dimethyl 5-sodium sulfoisophthalate nanoparticles were wrapped around the recycled poly(ethylene terephthalate) yarn by means of a novel electrospinning technique. Several tests were performed to investigate the parameters affecting wicking rise and moisture regain of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Wicking, the absorption capacity and passive spreading of liquid into the narrow micro/nano-spaces without the action of external forces, plays a crucial role in the processing procedures and the potential applications in many fields including but not limited to bioinspired textiles, 13 thermal management, 4,5 moisture harvesting, 6 oil recovery, 7 particle filtration, 8 biomedical, 911 tissue engineering scaffolds, 12 microfluidic devices, 13 geotextiles, 14,15 etc. In these materials, the wicking behavior alters if there is any change in the fluid characteristics, the surface treatments, and structural geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Wicking, the absorption capacity and passive spreading of liquid into the narrow micro/nano-spaces without the action of external forces, plays a crucial role in the processing procedures and the potential applications in many fields including but not limited to bioinspired textiles, 13 thermal management, 4,5 moisture harvesting, 6 oil recovery, 7 particle filtration, 8 biomedical, 911 tissue engineering scaffolds, 12 microfluidic devices, 13 geotextiles, 14,15 etc. In these materials, the wicking behavior alters if there is any change in the fluid characteristics, the surface treatments, and structural geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the height of wicking was about 12.17 mm in S4 sample, which was more than reported by Abbaszadeh et al (3 mm) and Ravandi et al (10 mm). [ 13,14 ] As well it was less than the maximum height of wicking in the work of Liu et al and Jin et al, which was reported 76 and 20 mm, respectively. [ 17, 18 ]…”
Section: Resultsmentioning
confidence: 89%
“…Polymer concentration, the mass ratio of nanoparticles, take‐up speed, and the number of filaments are the main factors that affect the wicking rate. [ 13 ] Hosseini Ravandi et al studied the wicking ability of the polyacrylonitrile/titanium oxide (PAN/TiO 2 ) nanofiber yarn using colored liquid. The yarn with a lower twist had a higher rate of capillary rise.…”
Section: Introductionmentioning
confidence: 99%
“…Latifi et al obtained a nanofiber web with recycled PET and nano iron oxide via electrospinning, which possesses microwave absorption characterization and wettability [ 107 ]. Alirezazadeh and colleagues electrospun a micro/nanofibrous core-sheath yarn with recycled PET wrapped by PAN containing dimethyl 5-sodium sulfoisophthalate nanoparticles and examined its wicking behavior for filtration [ 108 ]. Vanegas et al revealed that electrospinning the recycled PET and zinc oxide nanoparticles together could obtain fibers with antibacterial and antifungal properties [ 94 ].…”
Section: Typical Polymer Waste and Reutilization Via Electrospinningmentioning
confidence: 99%